Conceptual Review of DoS Attacks in Software Defined Networks - Najmun, Nisa; Adnan Shahid, Khan; Zeeshan, Ahmad; Sehrish, Aqeel; Jamil, Asim; Shehroz, Afzal (2022)
Software-defined networking (SDN) is a new developing technology that has been widely adopted by businesses because of its low cost and greater innovation in networks specially Scaling or manually configuring physical infrastructure. This makes it easier to design networks and manage huge networks. Scaling or manually configuring physical infrastructure is a problem for older networks, which cannot keep up with today's rapid technological advancements. Another important issue is the lack of information and the absence of a skill set or experienced experts required with technological expertise, which is very much concerned about the current situation. For this reason, a software-defined network architecture has been developed that allows for a more flexible network that can be reconfigured to meet changing needs. However, there are also other security concerns to consider especially the controller’s security. In this paper, we examine the impact of Denial of Service (DoS) attacks on the SDN controller and different mitigation techniques to overcome these attacks. The research effort also points out possible future research on this topic, as well as its limitations.